A Phase 1 randomized study of GSK3732394, an investigational long-acting biologic treatment regimen for HIV-1 infection. Issue 5 (3rd October 2022) - Krystal, Mark; Chabria, Shiven; Austin, Daren; Wolstenholme, Allen; Wensel, David; Lataillade, Max; Abberbock, Judah; Baker, Mark; Ackerman, Peter
Background: The GSK3732394 multivalent protein was developed as a novel, long-acting, antiretroviral biologic treatment regimen with three independent, non–cross-resistant mechanisms for inhibiting HIV-1 entry. Methods: A single-centre, Phase 1, double-blind, randomized, placebo-controlled study was conducted in healthy volunteers, using a 2-part adaptive study design: in Part 1, participants were randomized to receive subcutaneous injection of GSK3732394 or placebo (3:1) as single ascending doses (10-mg starting dose); in Part 2, participants were intended to receive multiple ascending doses. Primary and secondary objectives included safety, pharmacokinetics (PK) and pharmacodynamics (PD; cluster of differentiation four receptor occupancy [CD4 RO]) of GSK3732394 in healthy adults; PK/PD results in healthy volunteers were used to project HIV-1 treatment success. Results: The most frequently reported adverse event was injection site reactions (ISRs; 8/18 [44%]). Most ISRs were mild (Grade 1–2; n = 7); one participant experienced a Grade 3 ISR (erythema ≥10 cm). All ISRs were delayed in onset (after Day 10). GSK3732394 demonstrated linear PK across all cohorts. Clearance was faster than expected, and PK/PD results were lower than expected, with the maximum dose investigated (80 mg) achieving mean trough CD4 RO of ∼25% on Day 7. The study was terminated as the PK/PD model linking PK and CD4 RO indicated that the maximum planned doses would not achieve the desired therapeutic profile. Conclusions: This study demonstrated successful deployment of PK/PD dose relationships in the design and conduct of clinical trials by leveraging the findings toward predicting probability of success, resulting in appropriate early termination (ClinicalTrials.gov, NCT03984812).